Effective accessibility: Using effective speed to measure accessibility by cost. (March 2020) - Vale, David
Highlights: By ignoring travel cost, car accessibility might be overstated. When planning for accessibility, mobility management policies should be reflected. Effective speed can be used as the impedance value to measure accessibility by cost. Effective accessibility is able to express socio-spatial inequalities.